“The Knowledge of God: A Biblical-Theological Analysis of the Term Yada (ידע).” (Theological Kronos, 2020)
This article is a biblical theological analysis of the Yadah term “knowing” based on Hosea 6: 6. It is a contribution to the understanding of what the concept of “knowledge of God” encompasses. It includes an approach and possible solution to the antagonism existing between the different ways of approaching: experiencing and knowing, bearing in mind that there must also be a relationship with divinity, and proclamation of God who does not know him.An etymological analysis is intended, which is complemented by a biblical theological approach to understand “knowing” God and perceiving that there is no one way to approach that knowledge and practicing it as the only way is not sufficient itself if what you want is a knowledge as it is contained in the object of study term.
Keywords: Knowledge; experience; intellect; relationship; proclamation